Antibacterial Activity of Averrhoa bilimbi and Cananga odorata Infusions Against Cutibacterium acnes - Rahmawati Rahmawati; Zulfa Zakiah; Anggi Ghina Aulandari (Jurusan Farmasi Universitas Negeri Gorontalo, 2026)
Acne is a common skin disorder often associated with infection by Cutibacterium acnes. The long-term use of synthetic antibiotics such as clindamycin may cause adverse effects and contribute to bacterial resistance, highlighting the need for alternative natural treatments. This study evaluated the antibacterial activity of infusions of belimbing wuluh leaves (Averrhoa bilimbi Linn.) and kenanga flowers (Cananga odorata (Lam.) Hook.f. Thomson), administered individually and in combination, against the growth of C. acnes. The study was conducted experimentally using seven treatments: positive control (clindamycin), negative control (sterile distilled water), single infusions of belimbing wuluh leaves and kenanga flowers, and combination infusions at ratios of 2:1, 1:2, and 1:1. Antibacterial activity was assessed using the disc diffusion method. All infusion treatments showed antibacterial activity in the moderate category, with mean inhibition zones of approximately 6-7 mm. Under the present disc diffusion conditions, the combination infusions did not demonstrate greater antibacterial activity than the corresponding single infusions. Inhibition zones of the infusion treatments tended to decrease after 48 hours of incubation, which may reflect reduced persistence of activity, regrowth, compound instability, or other diffusion-related factors. These findings indicate that belimbing wuluh leaf and kenanga flower infusions possess antibacterial activity against C. acnes and may serve as potential natural anti-acne agents, although further studies using MIC/MBC, checkerboard, time-kill, and stability testing are required to clarify their interaction and antibacterial characteristics.